Digital discourse language in the new media - Thurlow, Crispin; Mroczek, Kristine R. (Oxford studies in sociolinguistics, 2011)
Chapters cover a range of communicative contexts (journalism, gaming, tourism, leisure, performance, public debate), communicators (professional and lay, young people and adults, intimates and groups), and languages (Irish, Hebrew, Chinese, Finnish, Japanese, German, Greek, Arabic, and French).